Bone Adaptation Process on Post-menopausal Women after Speed Play Walking Exercise with Medium & High Increased Cadence - Tinduh, Damayanti; Rosita, Primadita Esther; Mei Wulan, Sri Mardjiati (Faculty of Medicine, Universitas Airlangga, 2025)
Background: Postmenopausal period is usually marked by dominancy of osteoclast activity, which leads to a decrease in bone mass. Speed Play Walking Exercise (SPWE) could be an important mechanical strategy for maintaining bone cell activity in postmenopausal women. Aim(s): This study evaluated the rate of increased cadence in SPWE, which can reduce bone resorption and increase bone formation activities, associated with body mass index. Material and methods: This was four group pre-post intervention design randomized clinical trial, included 32 postmenopausal women in normal-weight (NW) vs. overweight (OW) groups, divided into 2 groups of different walking speeds. The intervention is SPWE method with increased 15-35% or 50-80% from initial cadence as intervention target cadence, alternated with usual cadence, 3 times a week, for 4 weeks duration. Variables are baseline CTx and NMid osteocalcin serum taken on pre and post 4 weeks exercise. Result: sNMid osteocalcin was increased in groups walked with 15-35% increased cadence compared to group walked with 50-80% increased cadence (p=0.002 for NW group and p=0.042 for OW group, respectively). NW group walked with 50-80% increased cadence showed the most decreased bone formation marker (p=0.019). CTx/NMid ratio is reduced in NW group walked with 15-35% increased cadence, on the other hand, OW group walked with 50-80% increased cadence showed the most increased trend of CTx/NMid ratio. Conclusions: To maintain bone formation activity, SPWE with a rate of 15-35% increased from initial cadence is suggested for postmenopausal women, however the benefit is more visible in women with normal-weight.